The Riddle of the Sands - Childers, Erskine (Saga Egmont, 2024)
Do you like Stieg Larsson\'s \'Millennium\', James Bond and dystopian dramas like \'The Man in the High Castle\'? The 1903 spy thriller \'The Riddle of the Sands\' has elements of all three - and then some. Ken Follett, author of \'The Pillars of the Earth\', called \'The Riddle of the Sands\' the \"first modern thriller\". It centres on a suspected plot by the German Empire to invade Britain. The plot proved to be almost prophetic, bearing in mind what was to follow in the First World War and the Second World War in the coming decades. Minor civil servant Carruthers and his friend, Davies are the men investigating the plot while on a yachting holiday in the Baltic Sea. They are drawn into an intricate story that includes secret treasure, a British traitor and a race against time to save Britain from the grip of the Kaiser. In 1979 \'The Riddle of the Sands\' was made into a spy thriller movie, starring Michael York, Jenny Agutter and Simon MacCorkindale. Childers\' technique of including a great deal of detail that could be verified was later used by authors including: John Buchan, who wrote \'The Thirty-Nine Steps\'; \'James Bond\' author Ian Fleming and John Le Carré. Erskine Childers (1870-1922) was an Anglo-Irish writer whose only true literary success came with \'The Riddle of the Sands\'. Instead, he found infamy through his political activism. Having been a prospective Liberal parliamentary candidate, he left the party and took up the cause of Irish Republicanism. He smuggled guns into Ireland on his yacht, but was executed during the Irish Civil War. His son, Erskine Hamilton Childers, became the 4th president of Ireland.